It's a blast! chilling and freezing in food production - Skok, Stephen; Video Educational Australasia (Australia : Video Educational Australasia, 2001)
This program looks at cutting edge technologies used to blast chill and blast freeze fresh and cooked food and its regeneration in a controlled cooking climate oven
Title from title screen
Executive producer, Neil Barrett ; editor, Deb Agars ; graphic, Reece Sanders ; camera, Tim Mummery, Leigh Tilson
Presenter: Andrea Waycott
Keywords: Frozen foods; Frozen foods industry